Phase Estimation of Single Tones Next to Modulated Signals in the Medium Frequency R-Mode System - Grundhofer, Lars; Wirsing, Markus; Gewies, Stefan; Galdo, Giovanni Del (IEEE Access, 2022)
Position, navigation, and timing information are critical to today's infrastructures; as a result, the possibility of estimating ranges is being explored in more and more radio systems. One way to achieve this is to extend the modulation with time-synchronised aiding carriers and to estimate their phase at the receiver side. In this paper, we present two ways to minimise the negative influence of the modulation on the phase estimation. We show that the classical maximum likelihood estimator is still an efficient estimator for our problem, using a medium-frequency R-Mode signal as an example, and is therefore used in receiver designs. We then describe two possible ways to precondition the signal to increase the accuracy for short observations. As a first approach, we describe how window functions can positively change the signal-to-noise ratio for our estimation. As a second approach, we show the use of a narrowband bandpass filter. Finally, we show that these approaches, applied to real measurements, improve the variance of the estimate by up to two orders of magnitude.
CRIS-Team Scopus Importer:2025-11-10
Keywords: APNT; navigation; phase estimation; R-Mode; signal processing